Implementasi Pengelolaan Guru dan Tenaga Kependidikan dalam Peningkatan Kualitas Pendidikan Berdasarkan (IASP) Tahun 2020 - Muhamad Badar Badrudin; Mulyawan Safwandy Nugraha (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study examines the implementation of teacher and education personnel management in improving the quality of education at MTsN 3 Subang based on the 2020 Education Unit Accreditation Instrument (IASP). This study aims to analyse the effectiveness of the management of teachers and education personnel in improving the quality of education. The research methods used include interviews, observations and documentation studies with samples of teachers, madrasah heads and education personnel. The findings show that transparent management in recruitment, regular coaching and objective performance appraisal contribute significantly to improving the quality of education. Adaptive and innovative management encourages madrasahs to become pioneers in various educational innovations. The contribution of this research provides an effective management model that can be adopted by other madrasahs to improve the overall quality of education.